Cytokine profiles in early rejection following OKT3 treatment in liver transplant patients - Sasan Roayaie; Patricia A. Sheiner; Sukru Emre; Steven Guy; Myron E. Schwartz; Peter Boros; Charles M. Miller (Mediators of Inflammation)
OKT3, a murine monoclonal antibody specific to the human CD3 complex, induces immunosuppression by depletion of T cells. Administration of OKT3 results in significant release of proinflammatory cytokines, such as TNFα and IL1β. Liver recipients who experience rejection within 3 weeks after transplantation with OKT3 prophylaxis recover their T cells by postoperative day 10 despite complete initial clearance.